2011
DOI: 10.3855/jidc.1441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of infectious bronchitis and Newcastle disease virus among domestic and wild birds in H5N1 outbreaks areas

Abstract: Introduction: The first H5N1 outbreak in Burkina Faso was reported to the World Organization for Animal Health on 3 April 2006. This study aimed to determine the prevalence of avian influenza virus, infectious bronchitis virus, and Newcastle disease virus among domestic and wild birds in highly pathogenic avian influenza (HPAI) H5N1 outbreaks areas. Methodology: We collected paired tracheal and cloacal swabs from 283 birds including 278 domestic and five wild birds (three vultures, one sparrowhawk and one West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…We included sequences in public databases representing all genotypes described so far and new isolates obtained and sequenced in this study in the framework of an international survey on wild and domestic birds in Africa. In this active surveillance survey, the prevalence of NDV in domestic birds was three times lower than that found in a study carried out in Burkina Faso [48]. In that study, the Burkina samples were also tested for the presence of influenza A viruses; the prevalence was estimated to be 3.2%.…”
Section: Discussionmentioning
confidence: 63%
“…We included sequences in public databases representing all genotypes described so far and new isolates obtained and sequenced in this study in the framework of an international survey on wild and domestic birds in Africa. In this active surveillance survey, the prevalence of NDV in domestic birds was three times lower than that found in a study carried out in Burkina Faso [48]. In that study, the Burkina samples were also tested for the presence of influenza A viruses; the prevalence was estimated to be 3.2%.…”
Section: Discussionmentioning
confidence: 63%
“…Two pairs of these primers and another pair of conserved primers reported previously [29], (Table 1) were successful in the amplification and sequencing of three regions of the viral 1b genes. The three regions were designated as 1b1 (848 bp), 1b2 (736 bp), and 1b3 (560 bp), corresponding to positions 15058–15921, 18164–18927, 14235–14756, respectively, in the genome (Figure 1).…”
Section: Resultsmentioning
confidence: 95%
“…Between 1994 Two years later, in Burkina Faso, Tarnagda et al (2011) confirmed during a study on avian diseases [avian influenza virus (AIV), IBV and Newcastle disease (NCDV)] in domestic and wild birds in highly pathogenic avian influenza outbreaks areas that the prevalence of IBV was 3.9% and no co-infection by AIV, IBV, and/or NCDV was found.…”
Section: Infectious Bronchitis Virus In West Africamentioning
confidence: 99%